Promise, trust and betrayal: Costs of breaching an implicit contract - Daniel C. Levy; Andrew T. Young (Bar-Ilan University, Department of Economics, 2020)
We study the cost of breaching an implicit contract in a goods market. Young and Levy (2014) document an implicit contract between the Coca-Cola Company and its consumers. This implicit contract included a promise of constant quality. We offer two types of evidence of the costs of breach. First, we document a case in 1930 when the Coca-Cola Company chose to avoid quality adjustment by incurring a permanently higher marginal cost of production, instead of a one-time increase in the fixed cost. Second, we explore the consequences of the company's 1985 introduction of "New Coke" to replace the original beverage. Using the Hirschman's (1970) model of Exit, Voice, and Loyalty, we argue that the public outcry that followed New Coke's introduction was a response to the implicit contract breach.
Keywords: E31; K10; L11; L16; L66; M20; M30; N80; N82; 330; Invisible Handshake; Implicit Contract; Customer Market; Long-Term Relationship; Cost of Breaching a Contract; Cost of Breaking a Contract; Coca-Cola; New Coke; Exit; Voice; Loyalty; Nickel Coke; Sticky/Rigid Prices; Cost of Price Adjustment; Cost of Quality Adjustment